Rebellions against the Great King in the Achaemenid Empire: Some Remarks - Podrazik, Michał (Anabasis. Studia Classica et Orientalia, 2017)
<p class="CDt4Ke zfr3Q" dir="ltr" style="background-color: transparent; line-height: 1.92; margin-bottom: 0; margin-left: 0; margin-top: 11pt; text-align: justify; text-indent: 15pt; white-space: normal; border: none; padding: 0;">On October 30-31 of 2014, at Yale University, took place the scientific conference entitled In the Crucible of Empire. Resistance, Revolt and Revolution in the Greco-Roman World. As the outcome of the conference a book edited by J.J. Collins and J.G. Manning, entitled Revolt and Resistance in the Ancient Classical World and the Near East. In the Crucible of Empire, was published (Leiden/Boston 2016, published in the series Culture and History of the Ancient Near East, vol. 85). The book constitutes an important contribution to the study of various disturbances in the Ancient World. One part of the book concerns the Achaemenid Persian Empire. And to this part of the book the present article refers to, with particular focus on, and discussion with the text by J.W.I. Lee entitled ‘Cyrus the Younger and Artaxerxes II, 401 BC: An Achaemenid Civil War Reconsidered’. The other texts discussed in the article are: ‘Xerxes and the Oathbreakers: Empire and Rebellion on the Northwestern Front’ by M. Waters, and ‘Resistance, Revolt and Revolution in Achaemenid Persia: Response’ by E.R.M. Dusinberre. <p class="CDt4Ke zfr3Q" dir="ltr" style="background-color: transparent; line-height: 1.92; margin-bottom: 0; margin-left: 0; margin-top: 11pt; text-align: justify; text-indent: 15pt; white-space: normal; border: none; padding: 0;">The war between the two brothers, Cyrus the Younger and Artaxerxes II, discussed by J.W.I. Lee in his text was a highly significant event in the history of the Achaemenid Empire. The text offers a very valuable and necessary outlook on this war, presented from the perspective of individual ‘lesser players’ (such as, for example, Abrokomas, or Syennesis and his wife Epyaxa), their personal interests and calculations in face of the armed conflict between the two brothers. <p class="CDt4Ke zfr3Q" dir="ltr" style="background-color: transparent; line-height: 1.92; margin-bottom: 0; margin-left: 0; margin-top: 11pt; text-align: justify; text-indent: 15pt; white-space: normal; border: none; padding: 0;">In the Achaemenid Empire rebellions against the Great King and Persian rule took place many times. The examples presented in the article, discussed by J.W.I. Lee, M. Waters, and E.R.M. Dusinberre, show how different was their nature, effect and importance. They also show how different the interpretation of such an events might be, depending on the adopted perspective and analyzed sources.